THE HISTORY OF ERECTILE DYSFUNCTION STUDY - Помешкин, Евгений Владимирович; Кызласов, Павел Сергеевич; Мартов, Алексей Георгиевич; Абдулхамидов, Александр Нурмагомедович; Осмоловский, Борис Евгеньевич; Кажера, Анастасия Андреевна; Забелин, Максим Васильевич (Medicine in Kuzbass, 2017)
This article presents a review of literature on the history of the study of theerection phenomenon and erectile dysfunction (ED). In the article the evolution of ED studiesis reviewed in a chronological order. Erectile dysfunction has been a major concern at all times. In the process of human development the knowledge of anatomy, physiology of the penis, the erection phenomenon and causes of erectile dysfunction as well asthe methods of treatment of this disease have been improved. The parallel development of different concepts, organic, hormonal and psychological theories has led to a common understanding that there is no a single mechanism of erection and there is no one factor influencing the occurrence of erectile dysfunction. Thus, there is no any single treatment for this disease. Currently clinical practice and research require an integrated approach to the problem of ED, multidisciplinary approach to diagnosis and treatment of erectile dysfunction with close cooperation of doctors of different specialties.
Keywords: erectile dysfunction; erectile dysfunction history; erection; impotence; male disease